2022
DOI: 10.3390/jcm11051334
|View full text |Cite
|
Sign up to set email alerts
|

Graft Failure Due to Nonadherence among 150 Prospectively-Followed Kidney Transplant Recipients at 18 Years Post-transplant: Our Results and Review of the Literature

Abstract: Background: We previously reported that graft failure due to nonadherence (GFNA) was a major cause of graft loss in kidney transplantation. Here, among 150 prospectively-followed kidney transplant recipients at 18 years post-transplant, we provide: updated (longer-term) estimates of cause-specific graft loss probabilities, risk factors for developing GFNA, and detailed characterizations of patients’ overt nonadherent (NA) behavior, including timing, extent, and clinical consequences. Methods: Determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…This result indicates that nonadherence is a significant risk factor for graft failure and it associated with poor graft survival. This finding is well supported by the literature [33][34][35]. Patient education, counseling, and support systems are crucial in promoting adherence to immunosuppressive medications and post-transplant care, thereby improving graft survival.…”
Section: Discussionsupporting
confidence: 64%
“…This result indicates that nonadherence is a significant risk factor for graft failure and it associated with poor graft survival. This finding is well supported by the literature [33][34][35]. Patient education, counseling, and support systems are crucial in promoting adherence to immunosuppressive medications and post-transplant care, thereby improving graft survival.…”
Section: Discussionsupporting
confidence: 64%
“…For example, in adult kidney transplantation, we recently reported that the estimated cumulative incidences of graft loss due to overt nonadherence and graft loss without overt nonadherence were 0.288 and 0.443 at 18 years posttransplant, respectively, among 82 patients who were aged <50 years at transplant. 28 Overall graft survival at 18 years posttransplant was estimated for this subgroup to be 0.269 (1.00 – [0.288 + 0.443]). A clinician might therefore want to suggest to a newly transplanted recipient aged <50 years that conditional on his or her not previously experiencing graft loss due to overt nonadherence (i.e., avoiding overt nonadherence), graft survival at 18 years posttransplant would be estimated to improve to 0.378, that is, 0.269 / (1.0 − 0.288).…”
Section: Statistical Methods: Modern Competing Risks Formulas and Heu...mentioning
confidence: 99%
“…(11) Evidence shows a gradual decline in adherence with prolonged length of posttransplant duration, resulting in a higher incidence of late acute rejection among nonadherence. (12,13) Like in any other condition, medication nonadherence in KTRs increases with the number of medications prescribed. (14) Social support plays a role in the adherence rate, with married people showing higher levels of adherence than single individuals.…”
Section: Introductionmentioning
confidence: 99%